OPTIMALISASI ZAKAT PRODUKTIF DALAM PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH - Irsyad, Adnan; Hafidhuddin, Didin; Ayuniyyah, Qurroh (Universitas Ibn Khaldun Bogor, 2022)
MSMEs are the backbone of the Indonesian economy, besides that, productive zakat is an instrument that can be used to save MSMEs from being destroyed by the pandemic. The effect between the both is important to know in order to encourage efforts to empower MSMEs. This study was made with the aim of knowing the distribution model of productive zakat in “Desa Berdaya” programs conducted by Rumah Zakat and to determine its effect on empowering MSMEs in the assisted villages. The results of this study found that the “Senyum Mandiri” program provided by Rumah Zakat through the digitization of MSMEs had a significant positive effect on empowering MSME mustahik in the assisted villages in Kel. Cipinang Muara, East Jakarta.